2019
DOI: 10.1155/2019/1504371
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problems and Associated Factors among Patients Admitted with Chronic Kidney Disease at Jimma University Medical Center, Jimma Zone, Jimma, Southwest Ethiopia: A Hospital-Based Prospective Observational Study

Abstract: Background There is an alarming rise of chronic kidney disease prevalence globally associated with significant morbidity and mortality necessitating special attention as one of the major growing public health problems. Medication-related problems are common in hospitalized patients including chronic kidney disease and may lead to increase hospital stay and health care cost and augment the risk of morbidity and mortality. Objective To determine prevalence of medication-related problems and associated factors am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 42 publications
9
55
0
Order By: Relevance
“…In addition, two‐thirds of the studies used prospective designs except for Haymen et al, 27 Yohanes et al, 28 Abadir et al, 39 and Hailu et al 29 studies. More than half (n = 10) of the included studies investigated one or more cardiovascular disease conditions, 15,28,32,35,36,39‐42 while Gebre et al, 43 Aster et al 44 and Beshir et al 18 studied ambulatory diabetic patients, hospitalized chronic kidney disease patients, and ambulatory epileptic patients, respectively. Moreover, Haymen et al 27 and Hailu et al 29 targeted ambulatory type II diabetes mellitus patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, two‐thirds of the studies used prospective designs except for Haymen et al, 27 Yohanes et al, 28 Abadir et al, 39 and Hailu et al 29 studies. More than half (n = 10) of the included studies investigated one or more cardiovascular disease conditions, 15,28,32,35,36,39‐42 while Gebre et al, 43 Aster et al 44 and Beshir et al 18 studied ambulatory diabetic patients, hospitalized chronic kidney disease patients, and ambulatory epileptic patients, respectively. Moreover, Haymen et al 27 and Hailu et al 29 targeted ambulatory type II diabetes mellitus patients.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies, Mohammednur et al 41 and Beshir et al, 18 reported clinical outcomes of MRPs (Table 2). Further, seven studies 27‐29,42‐45 reported the specific causative agents (drugs) responsible for MRPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the total included studies, eight studies were conducted in Jimma University Medical Center (JUMC) [26][27][28][29][30][31][32][33], seven were conducted in Tikur Anbesa Specialized Hospital [25,[34][35][36][37][38][39]. Three studies were conducted in Hiwot Fana Specialized University Hospital [40]- [42] and two studies were conducted in Dessie Referral Hospital [43,44].…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…On the other hand, the educational intervention of patients by clinical pharmacists can improve patients' adherence to drug therapy. 11,19 Hence, improving drug therapy has an important effect on the patients' health, treatment costs, and enhancing patients' quality of life. 18 In developing countries, including Ethiopia, antimicrobials are used more frequently than any other drugs for both bacterial and non-bacterial infections.…”
Section: Introductionmentioning
confidence: 99%